Exploring adherence to antipsychotic medications in Hospital Kajang: a qualitative study / Wan Nur Asyiken Wan Ab. Rahman - Wan Ab. Rahman, Wan Nur Asyiken (2017)
Management of mental illness entails acute and long term treatment. This qualitative study explored the perspective of those patients prescribed with antipsychotic medication about their treatment and also to identify ways in which the healthcare system can facilitate the adherence. Thirty-five semi-structured, one to one interviews were conducted to explore the patient perception and experience on the disease management. Interviews were audio-recorded, transcribed verbatim and thematically analysed by the constant comparison method. The findings showed that patient’s perception, knowledge, belief and experiences will influence their medication-taking behaviour. However, the patient’s experience with the services and their socioeconomic background did not affect adherence. The healthcare professional believes education may help to increase adherence because the factors are modifiable. Healthcare services and the collaboration between the doctors, pharmacists and nurses were found helpful in ensuring the continuity of care which ultimately saves lives and unnecessary costs. The patients reported being more comfortable talking with the doctors and nurses about their medications compared with the pharmacists. The other healthcare professionals do encourage pharmacist to be part of them. Unfortunately, a pharmacy service in Hospital Kajang is not yet expanded in the psychiatric department due to lack of training and manpower. The findings were in line with Health Belief Model when the medication-taking behavior and adherence was influenced by patient’s belief and perception. As a conclusion, the researcher found that the patients, caregivers and the healthcare professionals do not have a shared understanding of which factors are important in medication adherence behaviour and the strategies to improve them. The study identifies that providing relevant information to patients and their families, together with pharmacists participation in managing antipsychotic medication may help to facilitate adherence among patients in Hospital Kajang.